Faktor-faktor yang Memengaruhi Resiliensi Mahasiswa Kedokteran - Swasti, Ni Kadek Candra (Essence of Scientific Medical Journal; Vol 21 No 2 (2024): Volume 21 No. 2 (Juli - Desember 2023) Essential: Essence of Scientific Medical Journal, 2024)
ABSTRACT Introduction:  Resilience is the human ability to survive in difficult situations, be able to cope with challenges, and recover from failure. Medical fields are well-known to have work climates that inducing stress and associated with high tends of burnout. Therefore, medical students need high resilience. This article aims to analyze and summarize research findings regarding factors that influence medical student resilience. Discussion:  Various studies have been conducted to explore medical students experiences and strategies in increasing resilience. Several studies state that personal characteristics such as optimism, empathy, and personality are predictors of resilience. However, other studies explain that self-awareness and skills in using coping strategies  also  play a major role. Furthermore, external support from family,  significant others  and institutions plays a role in forming student resilience. Conclusion:  Based on the literature review, the factors influencing resilience of medical students are grouped into personal factors, namely personality traits, self-awareness, and coping strategies, and the other one are external sources, namely social supports, institutional supports, and religion. Keywords:  Resilience, Medical, Students